2018
DOI: 10.1111/jch.13319
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent rest may not be necessary for automated office blood pressure at lower treatment targets

Abstract: In SPRINT (Systolic Blood Pressure Intervention Trial), use of the Omron 907XL blood pressure (BP) monitor set at 5 minutes of antecedent rest to record BP produced an automated office BP value 7/6 mm Hg lower than awake ambulatory BP at 27 months.The authors studied the impact on automated office BP of setting the Omron 907XLto 0 minutes instead of 5 minutes of rest in patients with readings in the lower normal BP range, similar to on-treatment BP in the SPRINT intensive therapy group.Patients (n = 100) in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…The conclusions from our research are limited because of the different protocols used with the automated devices. For example, Colella et al reported a closer relationship between AOBPM and the mean awake ambulatory BP when the pre‐measure resting period was shortened from 5 to 0 minutes. It should also be stressed that probably only ~50% of measurements were truly unattended in the SPRINT trial .…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions from our research are limited because of the different protocols used with the automated devices. For example, Colella et al reported a closer relationship between AOBPM and the mean awake ambulatory BP when the pre‐measure resting period was shortened from 5 to 0 minutes. It should also be stressed that probably only ~50% of measurements were truly unattended in the SPRINT trial .…”
Section: Discussionmentioning
confidence: 99%
“…The AOBP values were found to be lower than awake ABP in both groups suggesting that office BP values in the lower range of normal were lower than the awake ABP. Taking these findings into account, Colella et al compared AOBP using the Omron HEM 907 monitor, with and without preceding rest, and concluded that in the lower normal range AOBP recorded without preceding rest should be higher and closer to the awake ABP although 24‐hours ABP was not performed. Consequently, we conducted this study to clarify whether AOBP readings, in treated and untreated hypertensives, can be used without a rest period using also awake ABP monitoring as a comparator.…”
Section: Introductionmentioning
confidence: 99%
“…2 Using this technique in SPRINT, office BP at target (120/66 mm Hg) was 7/6 mmHg lower than the corresponding awake ambulatory BP. 3 The results of our study 4 suggested that the Omron 907 without any antecedent rest should produce readings which more closely approximate the awake ambulatory BP, when systolic BP is in the target range of 120-130 mmHg. Dr Padwal 5 seems concerned about the variability of automated office (AO) BP.…”
Section: Response To the Letter To The Editor On "Antecedent Rest Maymentioning
confidence: 60%